An Intelligent Tutoring System (ITS) view on AOSE. (14th December 2007) - Vicari, Rosa Maria; Gluz, Joao Carlos
The creation of Intelligent Tutoring System (ITS) applications involves tasks that require the modelling of complex agents (i.e., human students); therefore, a cognitive agency approach is more appropriate than a weak agency approach. ITS applications need to know, plan and understand several aspects of the other intelligent entities that inhabit the same environment. This is the viewpoint not considered in Agent-Oriented Software Engineering (AOSE) methodologies that this work intends to cover. This aspect is the main innovation of this work, and also presents a critical requirement that should be fulfilled by applications before someone tries to use the AOSE methods proposed here. In this context, the paper presents a set of AOSE methods derived from ITS research, which defines applicability criteria, designs principles and implementation guidelines to be applied in the software analysis, design and development process. The application of such methods is exemplified by several ITSs developed in our research group.